Nonspecific Erysipelothrix rhusiopathiae Bacteremia in a Patient with Subclinical Alcoholic Liver Disease. (30th May 2013) - Kichloo, Asim Ahmed; Hallac, Alexander; Mousavi, Ben; Hirekhan, Omkar
Abstract : Erysipelothrix rhusiopathiae, a pleomorphic gram-positive bacillus, is found widely in nature or as a commensal pathogen. It infects domestic animals such as swine, which may be the major reservoir of the organism. E. rhusiopathiae is primarily an occupational illness; 89% of the cases are linked to high-risk epidemiological situations. Humans that are infected by this bacillus typically present with one or a combination of the following symptoms: localized skin lesion (erysipeloid), diffuse cutaneous eruptions with systemic symptoms, or bacteremia, which is often followed by endocarditis. We report a case of E. rhusiopathiae bacteremia that was present without severe clinical illness such as endocarditis, arthritis, or skin lesions. The patient was a 64-year-old male with a complicated past medical history including subclinical alcoholic liver disease. Penicillin-G therapy completely resolved the patients bacteremia. The case presented has exceptional clinical merit due to 2 key factors: the patient does not fit the occupational demographic typically affected by this bacterium, and the patient presented with subclinical septicemia, which has a high correlation with fatal endocarditis. This case brings a new prospective to E. rhusiopathiae bacteremia.